Islam dan Peradaban Spanyol: Catatan Kritis Beberapa Faktor Penyebab Kesuksesan Islam Spanyol - Sudirman Sudirman (UIN Maulana Malik Ibrahim Malang, 2011)
Born in the East, Islam was successfully expanded to Spain, a strong Christianity based country in the West. The civilization of this nation has encouraged the development of Europe in many ways, especially in the area of science and technology. The development of culture and civilization in Europe was undeniably connected to the existence of Islamic government in Spain. When Muslims rule this country many Europeans tempted to learn and study in Spain. At this classical period, Islam reached their golden era. Spain had become the central of Islamic civilization. From this fact, there are several important questions arise worth discussed in this essay, firstly, the background of the Islamic expansion to Spain and the dynamic development of Islam in this country that resulted in a great success. In this article, the writer applies historical approach using historical data from various history literature sources. In general, there are two conclusions. First of all, the expansion of Islamic government to Spain was motivated by the development of Islamic government in North Africa. Therefore, the expansion to Europe through Spain was unavoidable. Furthermore, Spain is the nearest region to North Africa and the power of Gothic Kingdom ruled this region was weakened. Second, the development of Islam in Spain was about 500 years and had reached its peak of supremacy when it was under the Abdurrahman III command. Although Islam, finally, was expelled from Spain after the fall of Islamic government, the Islamic culture has triggered European society renaissance. Islam yang lahir di dunia Timur pernah berjaya menguasai Spanyol, sebuah negara berbasis Kristen di Barat. Peradaban Spanyol telah berhasil memajukan kawasan Eropa di berbagai bidang, khususnya di bidang ilmu pengetahuan dan teknologi. Kemajuan-kemajuan Eropa tersebut tidak bisa dipisahkan dari keberadaan pemerintahan Islam di Spanyol. Dari Spanyol Islamlah Eropa banyak menimba ilmu. Pada periode klasik, ketika Islam mencapai masa keemasannya. Spanyol merupakan pusat peradaban Islam yang sangat penting. Dari kenyataan itu, ada sebuah pertanyaan yang layak untuk diangkat dalam tulisan ini, yakni latar belakang ekspansi Islam ke Spanyol dan dinamika perkembangan Islam di negara tersebut hingga pernah sukses besar membangun peradaban di sana. Tulisan ini, pendekatan yang digunakan adalah pendekatan historis dengan memanfaatkan bahan kajian dari literatur sejarah. Ada 2 kesimpulan tulisan ini yaitu pertama, latar belakang ekspansi Islam ke Spanyol didasari oleh semakin kuatnya Islam di Afrika Utara sehingga perlu melakukan perluasan ke Semenanjung Liberia. Spanyol adalah daerah terdekat dari Afrika Utara dan kerajaan Gothic yang menguasai daerah tersebut sedang mengalami kemunduran. Kedua, perkembangan Islam di Spanyol berlangsung sekitar 500 tahun dan pernah mencapai puncaknya saat di bawah kepemimpinan Abdurrahman III. Meskipun akhirnya Islam harus keluar dari Spanyol, peradaban peninggalan Islam telah membuat Eropa bangkit dari keterbelakangannya